Susceptibility profile of Anopheles and target site resistance mechanism against organophosphates in Cameroon. - Judith Dandi-Labou; Jonas A. Kengne-Ouafo; Leon Mugenzi; Magellan Tchouakui; Murielle Wondji; Charles S. Wondji (PLoS ONE, 2025)
Escalating pyrethroid resistance in malaria vectors jeopardizes vector control, necessitating the use of alternative insecticides such as pirimiphos-methyl (organophosphate) for indoor residual spraying (IRS). Tracking the spread of resistance and elucidating its molecular basis are essential for effective resistance management against these insecticides. This study monitored resistance to two organophosphates, malathion (MA) and pirimiphos methyl (PM), in three malaria vectors (Anopheles gambiae s.s., An. coluzzii, and An. funestus s.s.) across Cameroon and explored related resistance mechanisms. WHO tube assays revealed that An. funestus s.s. populations were fully susceptible to both organophosphates; An. coluzzii populations were either fully susceptible (North) or potentially resistant (South; 97% mortality). In contrast, the two An. gambiae s.s. populations in this study were resistant: in the rural agricultural hotspots of Mangoum (94% mortality to PM; 50% to MA) and in peri-urban cultivated location of Nkolondom, which exhibited the highest resistance to both PM (80% mortality) and MA (46% mortality), associated with recorded use of organophosphates by farmers. Genotyping the Ace-1 markers revealed a close association with susceptibility profile, as no resistance allele was observed in An. funestus s.s. and in the northern population of An. coluzzii and a very low frequency in Njombe (3%). In contrast, a higher frequency of Ace-1R was observed in An. gambiae s.s. with a significant association observed with resistance (PM: OR = 20.33, P = 0.04; MA: OR = 98.33, P = 0.0019). Furthermore, analysis of 100 Ace-1 clones showed copy number variation was linked to resistance, as resistant mosquitoes displayed higher copy numbers compared to susceptible individuals. These findings suggest that malaria control with organophosphate-based IRS is a viable alternative in Cameroon; however, it will be necessary to consider the distribution of species and the development of resistance.